The Association Between Adequate Prenatal Care and Severe Maternal Morbidity Among Teenage Pregnancies: A Population-Based Cohort Study - Nam, Jin Young; Oh, Sarah Soyeon; Park, Eun-Cheol (Frontiers in Public Health, 2022)
Background: This study aimed to examine whether the adequacy of prenatal care impacts the risk of severe maternal morbidity in teenage pregnancies. Methods: We included 23,202 delivery cases among adolescent mothers aged 13–19 years at ≥ 37 weeks’ gestational age. Data were derived from the National Health Insurance Service National Delivery Cohort in Korea between 2003 and 2018. We used a generalized estimating equation model and adjusted for numerous covariates to determine the adjusted relative risk (RR) associated with severe maternal morbidity. The primary outcome measures were severe maternal morbidity and the Kessner Adequacy of Prenatal Care Index score. Results: Severe maternal morbidity occurred in 723 (3.1%) of the 23,202 deliveries investigated. The risk of severe maternal morbidity was 1.8-fold higher among adolescent mothers who received inadequate prenatal care (RR: 1.81, 95% confidence interval [CI]: 1.39–2.37) and 1.6-fold higher among those who received intermediate prenatal care (RR: 1.59, 95% CI: 1.33–1.87) compared to those with adequate prenatal care. The synergistic effects of inadequate prenatal care and maternal comorbidities affected the occurrence of severe maternal morbidity. Conclusion: This study confirmed that inadequate prenatal care is associated with increased risk of severe maternal morbidity in pregnant teenagers. Notably, maternal comorbidities and inadequate prenatal care synergistically impacted severe maternal morbidity. Public health policy makers should focus on the development and implementation of programs that provide adequate prenatal care and financial/healthcare support to teenage mothers during pregnancy.